2020
DOI: 10.1093/europace/euaa279
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic risk assessment to improve quality of care in patients with atrial fibrillation: the 7th AFNET/EHRA Consensus Conference

Abstract: Aims The risk of developing atrial fibrillation (AF) and its complications continues to increase, despite good progress in preventing AF-related strokes. Methods and results This article summarizes the outcomes of the 7th Consensus Conference of the Atrial Fibrillation NETwork (AFNET) and the European Heart Rhythm Association (EHRA) held in Lisbon in March 2019. Sixty-five international AF specialists met to present new data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 40 publications
0
36
1
1
Order By: Relevance
“…Diseases or conditions such as diabetes mellitus, heart failure, and ageing (CHA2DS2VASc Parameters) are known to increase alterations by oxidative stress pathways within endothelial cells, and thereby further increase the expression of prothrombogenic molecules. These changes are not related to the presence of absence of AF, explaining why atrial thrombogenesis is still increased even during sinus rhythm in certain subgroups of patients [211,212]. Recently, post hoc studies from large randomized controlled trials suggested that the burden of AF (Figure 3) as well as the type of AF (paroxysmal versus persistent/permanent AF) might be a factor, which drives differences in patient outcome [213][214][215][216][217].…”
Section: Atrial Endocardial Remodeling As a Cause Of Thrombogenesis And Strokementioning
confidence: 99%
“…Diseases or conditions such as diabetes mellitus, heart failure, and ageing (CHA2DS2VASc Parameters) are known to increase alterations by oxidative stress pathways within endothelial cells, and thereby further increase the expression of prothrombogenic molecules. These changes are not related to the presence of absence of AF, explaining why atrial thrombogenesis is still increased even during sinus rhythm in certain subgroups of patients [211,212]. Recently, post hoc studies from large randomized controlled trials suggested that the burden of AF (Figure 3) as well as the type of AF (paroxysmal versus persistent/permanent AF) might be a factor, which drives differences in patient outcome [213][214][215][216][217].…”
Section: Atrial Endocardial Remodeling As a Cause Of Thrombogenesis And Strokementioning
confidence: 99%
“…For heart failure with preserved ejection fraction, this identification can be achieved by observing if patients respond well to diuretics (heart failure dominant) or rate control and cardioversion (AF dominant). Treatment of underlying factors would likely benefit heart failure dominant patients while AF dominant patients would benefit from antiarrhythmic therapies 4 . This approach is one of the promising avenues to personalise therapies in patients with concomitant AF and heart failure for better outcomes.…”
Section: Comissioned Editorial Bmj Heart Journalmentioning
confidence: 99%
“…Schätzungen zufolge wird zeitlebens jeder dritte heute 55-Jährige an Vorhofflimmern erkranken [1]. Vorhofflimmern ist mit gefährlichen kardiovaskulären Komplikationen assoziiert, insbesondere Herzinsuffizienz, Schlaganfall und kardiovaskulärem Tod [2]. Meilensteine der Behandlung von Vorhofflimmern, welche zur maßgeblichen Reduktion der Mortalität als auch Morbidität geführt haben, sind die ora- Abb.…”
Section: Update Vorhofflimmern: Die Esc-leitlinien 2020 Sowie Aktuellunclassified